Sleep high (2800 m) and train low (610 m): Effects on altitude-induced reductions in VO2peak in high level kayak athletes - Logan, P. A.; Martin, D. T.; Dixon, J.; Fornasiero, D.; Gawthorn, K.; Gore, C. J.; Hahn, A. G.; Kelly, B. P.; Roberts, A.; Slater, G. J.; Walker, J. (1999)
The purpose of this study was to determine whether a 2-week altitude camp (sleep high, train low) would effect the magnitude of the altitude-induced reduction in VO2peak in high-level kayak athletes. 10 athletes who were members of the AIS or National Sprint Kayak Squads completed the investigation. These athletes performed three multistage VO2max tests on a magnetically braked kayak ergometer (modified "K1 Ergo", Canberra, Australia) prior to the sleep high, train low period. The first of the ergometer tests was performed under normoxic conditions and served as a familiarisation trial while two subsequent tests were performed under hypoxic (1800m) and normoxic (0m) conditions. The latter two tests were again completed after the sleep high, train low period. The ergometer tests were conducted at 610m using inspired air enriched with either O2 (PO2 159 mmHg) or N2 (PO2 132 mmHg) which simulated the sea level and 1800m altitude conditions. Trials were randomised, counter-balanced and single blind. The sleep high, train low period lasted for 11 nights during which five athletes slept in an altitude simulation chamber under hypoxic conditions equivalent to 2800m above sea level (SHTL group). The remaining athletes slept at 610m (SLTL group). VE and VO2 (Ametek O2 and CO2 analysers, Tissot tanks), HR (Polar, Accurex Plus) and [La-] (arterialised blood from hyperaemic earlobe or fingertip - Radiometer ABL 625GL lactate analyser) were measured throughout each ergometer test. Mean VO2peak for both groups was lower during the hypoxic test in comparison with the normoxic test (^ alt, -0.49 and -0.66 L/min for the SHTL and SLTL groups respectively) prior to the sleep high train low period. However, this altitude-induced difference was unchanged after the sleep high, train low camp (^alt, -0.38 and -0.5 L/min). Similarly, the pre-camp differences in peak blood [La-] for the SHTL and SLTL groups between the normoxic and hypoxic tests (^ alt, 0.3 and -1.6 mmol/L) were unchanged after the training camp. These data indicate that a period of sleep high and train low does not result in a unique physiological response to high intensity exercise at moderate altitude for high-level kayak athletes.